11 Upcycling Bahiagrass Hay Using Cull Potatoes As an Alternative Feed Resource. (1st March 2018) - Hersom, M J; Wilson, T W; Warren, M; England, G K; Baggett, D
Abstract: A proof of concept demonstration was designed to evaluate the use of cull, table stock, chip potatoes (var. Atlantic) to upcycle low to marginal quality bahiagrass ( Paspalum notatum ) hay as an alternative feed resource for beef cattle producers. Two treatments were utilized; treatment one (Trt1) was a combination of 25% hay and 75% potatoes, 3.31 kg of hay and 9.99 kg of potatoes (as-fed basis) were combined; treatment two (Trt2) was a combination of 20% hay and 80% potatoes, 2.5 kg of hay and 9.99 kg of potatoes (as-fed basis) were combined. Two 208-L and one 132-L plastic barrels with lids were utilized for each treatment. Hay was peeled off of the bale and potatoes were rough chopped through a wood chipper. Hay and potatoes (DM = 93.5 and 70.5%, TDN = 61 and 85%, CP = 8 and 10%) were alternately layered into a barrel and compressed. After the sixth layer, barrels were sealed with a matching lid fitted with a check-valve and a vacuum applied to remove air. Barrels were opened and samples taken via a silage core-sampler after 72 d. Two cores from each barrel were collected for analysis. Comparisons of ensilage treatments was conducted with the Mixed procedure of SAS. The statistical model included ensiling treatment and replication. Least squares means are reported. Dry matter content did not differ ( P = 0.96, 32 ± 1.4%) between treatments and were 50% below the goal of a 60–65% DM product. Energy values did not differ ( P ≥ 0.17) on a DM basis, but were below expectation (TDN = 62.1 ± 2.04%, NEm = 0.26 ± 0.016 mcal/kg, NEg = 0.15 ± 0.015 mcal/kg) based on the proportions used. Crude protein was not different ( P = 0.47, 10.1 ± 0.49%) and greater than or equal to predicted. A nearly 50% greater ( P = 0.11) amount of starch in Trt2 compared to Trt1 indicated that fermentation of starch was limited. Limited fermentation is indicated by the similar ( P = 0.92) lactic acid, but nearly 50% decrease ( P = 0.06) in total acid production in Trt2 compared to Trt1. DMI potential, predicted from NDF, was similar ( P = 0.27, 13.5 ± 1.28 kg). This conclusion must be taken with caution as no measure of digestibility or intake was established. Proof of concept was successful with this demonstration. Upscaling to a small-scale, on-farm demonstration would seem necessary to validate this conclusion.